Bipolar disorder in a genetic isolate: Ancestry and subtypes of the disorder (2020)
ABSTRACT: Background: While broad, the current diagnostic category of Bipolar Disorder (BD) may not cover or describe the full clinical spectrum of this clinical condition. One potentially important factor lacking in previous research is the exact ancestral composition of the clinical samples. Objective: To define subtypes of BD in a genetic isolate (paisa population) using sociodemographic, clinical and ancestral composition variables, in efforts to generate various conglomerates that might be useful for determining the natural history of BD. Methods: We performed a cross-sectional study on a clinical sample of 164 patients diagnosed as Bipolar I or Bipolar II disorder as defined by DSM-IV-TR. Latent Classes Analyses were used to examine the interaction of the ethnic composition of the sample, rigorously defined using specific genetic markers, with clinical variables (number of previous episodes) and the therapeutic response to treatment with lithium. Results: the best fitting model resulting from the analyses consisted of six latent classes (LC) including ancestry composition, number of depressive and manic episodes, and clinical response to lithium treatment: LC-1 consisted of patients with predominantly European ancestry, having a small number of clinical episodes of mania/depression, and showing a good response to lithium; LC-2 consisted of patients with predominant Amerindian ancestry, presenting few clinical episodes, and showing an intermediate response to lithium; LC-3 consisted of patients with predominant African ancestry, intermediate number of clinical episodes, and showing a poor response to lithium. LC-4 grouped patients with predominant Amerindian ancestry, with an intermediate number of clinical episodes, and showing a partial response to lithium; LC- 5 consisted of patients with predominant Amerindian ancestry, multiple clinical episodes, and showing a poor response to lithium; LC-6 consisted of patients with predominant European ancestry, multiple clinical episodes, and showing the best response to lithium. Conclusion: On the basis of these results, we propose six latent subtypes of BD. We show that a rigorously defined ancestry component significantly influences clinical and treatment outcomes. This latent classification may be useful in describing the genesis, course and evolution of this heterogeneous disorder and may lead to a more personalized management of individual cases